Cookies and clairvoyance : a magical bakery mystery - Cates, Bailey (Cates, Bailey. Magical bakery mystery., 2019)
Hedgewitch Katie Lightfoot is juggling wedding preparations, a visit from her father, and home renovations on top of her long hours at the Honeybee Bakery, where she and her aunt Lucy imbue their yummy cookies and pastries with beneficial magic. But when firefighter Randy Post is accused of murdering a collector of rarities, and his prints are on the statue that was used to kill the man, Katie steps in. Randy is not only Katie's fiancé's coworker, but also the boyfriend of fellow spellbook club member and witch Bianca Devereaux. Bianca and Declan are both sure Randy is innocent, and so is Katie. However, to prove it she'll have to work with ornery detective Peter Quinn again<U+2014>and this time around he knows she's more than your everyday baker.Hedgewitch Katie Lightfoot is juggling wedding preparations, a visit from her father, and home renovations on top of her long hours at the Honeybee Bakery, where she and her aunt Lucy imbue their yummy cookies and pastries with beneficial magic. But when firefighter Randy Post is accused of murdering a collector of rarities, and his prints are on the statue that was used to kill the man, Katie steps in. Randy is not only Katie's fiancé's coworker, but also the boyfriend of fellow spellbook club member and witch Bianca Devereaux. Bianca and Declan are both sure Randy is innocent, and so is Katie. However, to prove it she'll have to work with ornery detective Peter Quinn again<U+2014>and this time around he knows she's more than your everyday baker.